Strategic Marketing Plan for Remedies Postpartum Care Center: A Roadmap to Brand Awareness and Customer Loyalty - Paksi, Yanuar Buana; Indradewa, Rhian; Kustiawan, Unggul; Pamungkas, Rian Adi (Dinasti Publisher, 2025)
This study develops a strategic marketing plan for Remedies Postpartum Care Center in Jakarta, Indonesia, addressing the growing demand for specialized postpartum care services. The postpartum period is a critical phase for mothers, often accompanied by physical, emotional, and mental health challenges, yet comprehensive care services remain limited in Indonesia. The research aims to enhance brand awareness, build customer loyalty, and ensure financial sustainability by identifying target markets, customer needs, and effective marketing strategies. Using a mixed-method approach, the study combines qualitative and quantitative data, including surveys, interviews, and market analysis, to formulate a marketing mix strategy 7Ps framework (Product, Price, Place, Promotion, People, Process, and Physical Evidence). Results reveal that Remedies caters to diverse customer segments through tailored One Stop Solution and Partial Solution packages, supported by digital marketing strategies such as social media campaigns and a dedicated mobile app. Revenue projections indicate significant growth, from IDR 5.17 billion in Year 1 to IDR 23.46 billion in Year 5, demonstrating the financial viability of the proposed plan. The study concludes that a customer-centric approach, combined with personalized services and digital tools, can effectively address the underserved postpartum care market, ensuring long-term success and improved maternal health outcomes.